Structural study of thick hexaferrite films. (April 2020) - Koutzarova, T; Georgieva, B; Kolev, S; Ghelev, Ch; Krezhov, K; Kovacheva, D; Vertruyen, B; Closset, R; Tran, L-M; Zaleski, A
Abstract: We present details of the microstructural properties of Y- (Ba2 Mg2 Fe12 O22, Ba0.5 Sr1.5 Zn2 Fe12 O22, Ba0.5 Sr1.5 Zn2 Al0.08 Fe11.92O22 ) and Z-type (Sr3 Co2 Fe24 O41 ) hexaferrite thick films deposited by screen printing and drop casting on unpolished polycrystalline Al2 O3 substrates. The hexaferrites thick films obtained by drop casting exhibited considerable roughness and porousness compared with those obtained by screen printing. We found that the powders' morphology significantly affects the microstructure of the thick films formed by screen printing. The microstructural analysis of the thick films shows that their microstructure differs from that of the powders. Further, during the annealing process the grains in the thick films grow and form hexagonal particles, the latter having the largest size, best shape and being best observed in the case of the Ba2 Mg2 Fe12 O22 film.